Pengaruh Kompensasi Finansial Dan Motivasi Intrinsik Terhadap Kepuasan Kerja Pegawai Pada Kantor Dinas Koprasi Umkm Kota Medan - Muhammad Farhan Alyusri; Juliana Nasution (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
This study aims to determine the effect of financial compensation and intrinsic motivation on employee job satisfaction. This type of research is quantitative. The population used in this study is the Medan City Small and Medium Enterprises Office which employs 51 employees. Primary data is used as a data source. Data were obtained by distributing questionnaires directly to the interviewees. The data analysis technique used multiple linear regression to determine the magnitude of the influence of employee professional ethics, financial compensation and intrinsic motivation on employee job satisfaction. The results of this study indicate that financial compensation and intrinsic motivation on employee job satisfaction have a significant partial and simultaneous effect on employee job satisfaction data